Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1179/1743281214y.0000000179
|View full text |Cite
|
Sign up to set email alerts
|

Reduction properties of high alumina iron ore cold bonded pellet with CO–H2mixtures

Abstract: To understand the reduction process of pellets made from high alumina iron ore from Guangxi Zhuang Autonomous Region, kinetic experiments, X-ray diffraction examination and scanning electron microscope analysis were adopted. The results show that temperature, a critical factor, increasing from 850 to 1050uC can increase the reduction degree from 31?03 to 55?01%. With increasing hydrated lime addition, the reduction degree increases. Calcium oxide can participate in the solid reaction and affect the mineral str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Facing the risks of raw material shortages, China is working towards the feasibility of using domestic low grade/refractory iron ore resources. There is a large deposit in the Guangxi Zhuang Autonomous Region with an average of 43 wt.% Fe 2 O 3 and 25 wt.% Al 2 O 3 [156]. Rath et al [157] have reported on a low grade iron ore from India containing 51.6 wt.% Fe 2 O 3 , 17.6 wt.% SiO 2 and 4.3 wt.% Al 2 O 3 .…”
Section: Comparison With Low Grade Iron Oresmentioning
confidence: 99%
“…Facing the risks of raw material shortages, China is working towards the feasibility of using domestic low grade/refractory iron ore resources. There is a large deposit in the Guangxi Zhuang Autonomous Region with an average of 43 wt.% Fe 2 O 3 and 25 wt.% Al 2 O 3 [156]. Rath et al [157] have reported on a low grade iron ore from India containing 51.6 wt.% Fe 2 O 3 , 17.6 wt.% SiO 2 and 4.3 wt.% Al 2 O 3 .…”
Section: Comparison With Low Grade Iron Oresmentioning
confidence: 99%
“…13) The main reactions in the RHF are the reduction of iron oxide by solid carbon, post combustion of gas generated by reduction, and the gas combustion from the tuyere. As the metallization rate and residual carbon of the pellet are set, its coal consumption can be determined directly.…”
Section: Rhf Calculation Modulementioning
confidence: 99%
“…Currently, in many enterprises, instead of high-quality iron ore, iron ore with high alumina is widely put into production due to its low price. China imports several million tons of high alumina iron ore from Australia, India, South East Asia, and Africa every year, driven by the continued massive growth of steel production in China which is expected to continue for years to come [1]. Theory and practice have demonstrated that alumina cannot be reduced in a blast furnace, therefore, it cannot stain the hot metal and does no harm to steelmaking.…”
Section: Introductionmentioning
confidence: 99%